The Performance Measures of Islamic Banking Based on the Maqasid Framework - Abdul Razak, Dzuljastri; Mohamed, Mustafa Omar; Md Taib, Fauziah (2008)
It has been taken for granted that Islamic banking (IB) is only about avoiding riba. The objectives of Islamic banking have not been formally addressed. As such, the present conventional performance yardsticks being used by IB have focused largely on financial measures. Hence there is a need for developing other performance measures that would complement the financial objectives of IB. This paper therefore proposes the objectives of IB from the theory of Maqasid al-Shari’ah and, derives a model of IB performance measures based on these objectives. A behavioral approach operationalization method (Sekaran, 2000) is used to quantify the Maqasid into measurable IB performance indicators that are later used for testing on a sample of six Islamic banks. The banks are evaluated and ranked at three levels based on their: 1) performance ratios, 2) performance indicators and 3) the overall Maqasid Index. Key words: Maqasid al-Shari’ah, Operationalization,., Simple Additive Weighting (SAW) Maqasid Index.